A Focusing Algorithm in Automatic Microscope - LIANG Long-kai; ZHAO Jing; HE Yong-jun (Journal of Harbin University of Science and Technology)
The traditional autofocus algorithm with high time complexity has slow speed of calculation for the current high-definition images that lead to low efficiency of the focusing． To solve this problem，we improve auto focusing by improving focusing evaluation and focus searching． First，two evaluation functions based on gray change，namely gray zero comparison method and low gray value statistics method，are put forwarded． Then the proposed evaluation functions are applied to realize the variable step climbing search strategy． The experimental results show that the proposed method in two aspects of focusing efficiency and clarity are better than current methods．